Revisiting the Classics in Secondary Education: Intertextual and Inter-artistic relationship proposals - Tavares de Faria, Rui (2022)
This article presents a set of proposal for an intertextual and inter-artistic relationship between authors and novels from Classical Antiquity and the contents that, in the context of Literary Education, make up the Programs, the Curriculum Goals and the Essential Learnings of the subjects of Portuguese and Portuguese Literature, at the level of the 10th grade. Considering the chronological extension and the diversity of modes and literary genres listed in the aforementioned documents, the corpus of examples is limited to Portuguese novels from the medieval and Renaissance periods.